PENGARUH CURRENT RATIO, DEPT TO EQUITY RATIO, RETURN ON ASSET DAN TOTAL ASSET TURNOVER TERHADAP HARGA SAHAM PROPERTI DAN REAL ESTATE DI BURSA EFEK INDONESIA - Fathorrosi Fathorrosi; Sugeng Priyanto; Selamet Riyadi (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
This research aims to determine the influence of the variables Current Ratio, Debt To Equity Ratio, Return On Assets, and Total Asset Turnover on share prices in property and real estate companies. The population used in this research is property and real estate companies listed on the Indonesia Stock Exchange with a research observation period of 2018 - 2022. The sample selection used a purposive sampling method based on certain criteria that were adjusted to the objectives of the research problem. The number of samples used in this research was 43 from 87 companies. The data analysis technique used in this research is Multiple Linear Regression Analysis using SPSS version 26 program tools. The results of this research show that the Current Ratio and Debt To Equity have a negative and significant effect on stock prices. Return On Assets has a positive and significant effect on share prices. Meanwhile, Total Asset Turnover has no significant effect on share prices.